The future of mobility-as-a-service: trust transfer across automated mobilities, from road to sidewalk - Hunter, Jacob G.; Ulwelling, Elise; Konishi, Matthew; Michelini, Noah; Modali, Akhil; Mendoza, Anne; Snyder, Jessie; Mehrotra, Shashank; Zheng, Zhaobo; Kumar, Anil R.; Akash, Kumar; Misu, Teruhisa; et al. (Frontiers in Psychology, 2023)
While trust in different types of automated vehicles has been a major focus for researchers and vehicle manufacturers, few studies have explored how people trust automated vehicles that are not cars, nor how their trust may transfer across different mobilities enabled with automation. To address this objective, a dual mobility study was designed to measure how trust in an automated vehicle with a familiar form factor---a car---compares to, and influences, trust in a novel automated vehicle---termed sidewalk mobility. A mixed-method approach involving both surveys and a semi-structured interview was used to characterize trust in these automated mobilities. Results found that the type of mobility had little to no effect on the different dimensions of trust that were studied, suggesting that trust can grow and evolve across different mobilities when the user is unfamiliar with a novel AD-enabled mobility. These results have important implications for the design of novel mobilities.